Genetic Aspects of Preeclampsia and the HELLP Syndrome - Haram, Kjell (Hindawi Publishing Corporation, 2014)
Both preeclampsia and the HELLP syndrome have their origin in the placenta. The aim of this study is to review genetic factors involved in development of preeclampsia and the HELLP syndrome using literature search in PubMed. A familial cohort links chromosomes 2q, 5q, and 13q to preeclampsia. The chromosome 12q is coupled with the HELLP syndrome. The STOX1 gene, the ERAP1 and 2 genes, the syncytin envelope gene, and the −670 Fas receptor polymorphisms are involved in the development of preeclampsia. The ACVR2A gene on chromosome 2q22 is also implicated. The toll-like receptor-4 (TLR-4) and factor V Leiden mutation participate both in development of preeclampsia and the HELLP syndrome. Carriers of the TT and the CC genotype of the MTHFR C677T polymorphism seem to have an increased risk of the HELLP syndrome. The placental levels of VEGF mRNA are reduced both in women with preeclampsia and in women with the HELLP syndrome. The BclI polymorphism is engaged in development of the HELLP syndrome but not in development of severe preeclampsia. The ACE I/D polymorphism affects uteroplacental and umbilical artery blood flows in women with preeclampsia. In women with preeclampsia and the HELLP syndrome several genes in the placenta are deregulated. Preeclampsia and the HELLP syndrome are multiplex genetic diseases.